NEW ARABIC-LANGUAGE SOURCES ON THE HISTORY OF RELATIONS BETWEEN SHAMKHAL MAHDI KHAN OF TARKY AND BEIBULAT TAYIMIEV - Idrisov, Usup Magomedovic; Hanmurzaev, Ismail Ibragimovic (History, Archeology and Ethnography of the Caucasus, 2022)
The paper introduces new documentary sources on the history of conclusion of the political alliance between Shamkhal Mahdi Khan and an authoritative Chechen officer Beibulat Tayimiev. The analysis of the content of the letters was carried out based on textological, paleographic and historical-comparative methods. As part of the study, letters from Mahdi Khan, his nephew Muhammad Bey and Abdulkarim, the qadi of Bolshie Atagi, are reviewed. The correspondence, reconstructed on the basis of the newly discovered five letters of its authors, shows the complexity and inconsistency of the views of the subjects of negotiations on their goals and objectives, as well as the ambiguous position of their active participant and mediator, qadi Abdulkarim. In addition, the letters included in this correspondence reflect the historical and political views of Mahdi Khan as an integral part of his political program to restore the former power of the Tarkovsky Shamkhalate. The paper provides commentaries and explanations for the names and titles found in the translated documents. In addition, a detailed analysis of the text of the letters is given with an explanation of the current socio-political situation in the region; of no less importance is the internal personal motives of certain figures, prompting them to make decisions. Thus, through the disclosure of these motivations, the personification of history takes place. The documents under study significantly clarify the details and mechanisms of interaction between Shamkhal Mahdi Khan and Beibulat Tayimiev and other influential figures in Chechnya. The paper also reveals the political context of the correspondence. As a result of the study, we acquire a more complete picture of the events of 1828-1829 in the North-Eastern Caucasus, anticipating a new development of the Caucasian War.
Keywords: correspondence; Arabic-language letters; Shamkhal Mahdi Khan; Beibulat; Abdulkarim; Khan Mukhammad-bek; Engelhardt; Shakhbaz; Dagestan; Zasulak Kumykia; Chechnya